Case Report: Airway obstruction as a fatal complication of infantile hemangioma in newborns: the eye cannot see what the mind does not know - Liu, Xiaoliang; Ma, Li; Ma, Fan; Wan, JiaoJiao; Hu, Huanrui; Zhou, Kaiyu; Hu, Fan (Frontiers in Pediatrics, 2025)
BackgroundIn newborns, infantile hemangiomas (IHs) in the airway can present with rare life-threatening complications associated with airway obstruction, even without cutaneous hemangioma.Case reportOur female newborn exhibited stridor 1 day after her birth. Furthermore, 7 days after birth, she was admitted to the local hospital to receive phototherapy for neonatal jaundice. However, her stridor was not noted as being related to IH by the clinician during her hospitalization. She was transferred to our hospital at 14 days old because her stridor and condition deteriorated with severe breathlessness and respiratory failure. Computed tomography and flexible bronchoscopy identified obstructive airway IHs. Although a combination therapy of propranolol and corticosteroids was prescribed for 2 weeks, she still needed invasive mechanical ventilation. After a discussion by the multidisciplinary team, endoscopic resection was carried out to resolve her airway obstruction at 30 days old, but it failed. Finally, transcatheter interventional sclerotherapy successfully resolved her clinical conditions at 60 days old. She was discharged and received follow-up with propranolol treatment. Her clinical symptoms of airway IHs were completely resolved 1 year later.ConclusionsAirway IHs can rarely present with life-threatening conditions associated with airway obstruction without cutaneous hemangioma in newborns. This case report highlights that propranolol is the cornerstone treatment for airway IHs. For the first time, our findings suggest that transcatheter interventional sclerotherapy can be a valid additional treatment option.